“SLY AS A FOXO”: New Paths with Forkhead Signaling in the Brain - Maiese, Kenneth; Chong, Zhao Z.; Shang, Yan Chen (Current Neurovascular Research, 2007)
The Forkhead transcription factor FOXO3a has emerged as a versatile target for diseases that impact upon neuronal survival, vascular integrity, immune function, and cellular metabolism. Enthusiasm is high to fill a critical treatment void through FOXO3a signaling for several neurodegenerative disorders that include aging, neuromuscular disease, systemic lupus erythematosus, stroke, and diabetic complications. Here we discuss the influence of FOXO3a upon cell survival and longevity, the intricate signal transduction pathways of FOXO3a, insights into present disease models, and the potential clinical translation of FOXO3a signaling into novel therapeutic strategies.
Keywords: Amyotrophic lateral sclerosis